The impact of QRIS on transaction efficiency, income growth, and financial management in Palu MSMEs - Saputra, Muh. Rangga; Kadang, Juliana; Darman, Darman; Risendy, Rian (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2026)
This study aims to examine the effect of QRIS implementation on transaction efficiency, income growth, and financial management of micro, small, and medium enterprises (MSMEs) in Palu City. The data were collected through questionnaires completed by 91 MSME owners and analyzed using SmartPLS. The results indicate that QRIS makes a meaningful contribution to accelerating transaction processes and improving service convenience. The implementation of QRIS has also been shown to increase income by attracting more customers and boosting sales turnover. Furthermore, QRIS assists business owners in managing their finances more systematically through automatic transaction records and clearer cash flow monitoring. These findings confirm that QRIS plays an important role in supporting MSME performance in the digital era.